2019
DOI: 10.1080/09585192.2019.1579247
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protean careers on talent retention: examining the relationship between protean career orientation, organizational commitment, job satisfaction and intention to quit for talented workers

Abstract: To study the effect of protean careers on talent retention, operationalized as the intention to quit, this study explores two pathways between protean career orientation and intention to quit: a direct pathway, and an indirect pathway via organizational commitment and job satisfaction. The study draws upon a sample of 306 talented workers selected from 17 Spanish and Mexican multinational organizations. Protean orientation should be expected to be widespread among talented individuals which might represent a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 48 publications
0
58
1
3
Order By: Relevance
“…Furthermore, research has shown that people with PCA and BCA give greater focus to their career management and development which drives their vocational behavior (Lo Presti et al, 2018; Stauffer et al, 2019). More specifically, Redondo et al (2019) suggest that by taking ownership of their career choices, individuals operating with a PCA achieve positive psychological outcomes, including career and life satisfaction, and individual well-being. Similarly, Enache et al (2011) argued that individuals exercising a BCA would develop their “knowing-whom” competencies (Lo Presti et al, 2018), which would provide access other people, thereby enhancing their development and personal learning (Kim & Beehr, 2017; Lo Presti et al, 2018).…”
Section: Pca Bca and Subjective Career Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research has shown that people with PCA and BCA give greater focus to their career management and development which drives their vocational behavior (Lo Presti et al, 2018; Stauffer et al, 2019). More specifically, Redondo et al (2019) suggest that by taking ownership of their career choices, individuals operating with a PCA achieve positive psychological outcomes, including career and life satisfaction, and individual well-being. Similarly, Enache et al (2011) argued that individuals exercising a BCA would develop their “knowing-whom” competencies (Lo Presti et al, 2018), which would provide access other people, thereby enhancing their development and personal learning (Kim & Beehr, 2017; Lo Presti et al, 2018).…”
Section: Pca Bca and Subjective Career Successmentioning
confidence: 99%
“…Extant research has shown that a protean career attitude (PCA) and a boundaryless career attitude (BCA) are positively related to work-related outcomes such as a passion for work, organizational commitment and job satisfaction (Gulyani & Bhatnagar, 2017;Redondo et al, 2019). However, less attention has been given to understanding the outcomes of PCA and BCA on career-related outcomes (Wiernik & Kostal, 2019).…”
mentioning
confidence: 99%
“…However, in terms of evidence, the recent analysis of the elite-egalitarian dichotomy has actually helped the broader field move forward. We now know that being a part of a chosen elite (where membership is transparent and is known to the individual) has been found to impact how favourably such talent perceives the general HR practices to be (Marescaux et al, 2013), their pay levels (Dries and Pepermans, 2008); their (lower) intentions to quit (Dries et al, 2014;Khoreva et al, 2017;Redundo et al, 2019), and their levels of both affective commitment (Gelens et al, 2015), commitment to increased performance demands, and identification with their work units (Björkman et al, 2013).…”
Section: Enter the Global Talent Management Researchersmentioning
confidence: 99%
“…Among them, the protean career concept (Hall, 1996) has been characterised as having a career orientation driven by values as defined by an individual and career management approach that is directed according to those personal values. Several researchers have shed light on the importance of the protean career concept, and its role as a driver of career success (De Vos & Soens, 2008;Gubler et al, 2014;Hall, 1996) and new insights are coming up in recent literature (Cortellazzo et al, 2020;Rodrigues et al, 2019;Sultana & Malik, 2019;Redondo et al, 2019 ). A growing interest in this area stems from the fact that a protean mind set is essential in shaping perceptions and building confidence of employees when the job market is highly dynamic and unpredictable.…”
Section: Introductionmentioning
confidence: 99%